An experimental investigation of the effect of strain on the electrical conductivity of a shape memory polymer. (February 2016) - Khan, Fazeel; Singh, Kumar
Abstract: A thermally triggered shape memory polymer (SMP) was prepared by blending electrically conductive carbon black (CB) into the resin prior to curing. The CB filled composite can then be activated through resistive heating. With the aim of using such SMPs in reconfigurable structures and/or actuators, the effect of strain on the conductive nature of the SMP composite was investigated. The study has specifically focused on changes to conductivity in, i) the transverse direction during tensile elongation to assess the impact of the Poisson effect, and ii) in samples deformed in compression. The dynamic response characteristics of the electrically activated SMP were also tested to assess the feasibility of using the composite in tunable vibration damping applications. Findings have shown that the pattern of changes in the transverse conductivity, which is marked by an increase-decrease-increase sequence, resembles that seen in the axial direction. SEM imaging of the samples was performed along the axial and transverse axes of deformation and shows no anisotropy in the CB filler distribution. To demonstrate potential uses of a conductive SMP in the sub- T g temperature range, a discussion of a vibration damping application has been included.